KETAHANAN BALISTIK LEMBARAN BAJA PADA BERBAGAI SUDUT TEMBAK - Rusnaldy, Rusnaldy; Haryanto, Ismoyo; Iskandar, Norman; Anugra, Binar Ade; Zaedun, Ahmad (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2014)
Results of study on the performance of 0.4 mm mild steel plate when impacted by 4.5 mm diameter steel ogive-shaped projectile at 45o, 60o (oblique impact) and 90 o (normal impact) angles of attack are presented. The projectiles were fired at highest velocity using air riffle gun. The target-holding fixture was located at a distance of 2 m from the gun. Experimental results show that steel plate provides protection at 45o and 60o obliquity, but fails to provide protection at angle of attack of 90o (normal impact)